2017
DOI: 10.1097/nnd.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Empowerment, Workplace Environment, and Job Satisfaction in Nurses Employed in an Academic Health Science Center

Abstract: Study results support predicted relationships and can be used to guide interventions for, and development of, nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Studies have revealed that nurses with higher perceived power have increased job satisfaction (Kretzschmer et al, 2017;Orgambídezramos et al, 2017). The predictability of job satisfaction is significantly impacted by career achievement when this variable is assessed (Dahinten, Lee, & Macphee, 2016;Riley, Beal, & Lancaster, 2008).…”
Section: Structural Empowermentmentioning
confidence: 99%
“…Studies have revealed that nurses with higher perceived power have increased job satisfaction (Kretzschmer et al, 2017;Orgambídezramos et al, 2017). The predictability of job satisfaction is significantly impacted by career achievement when this variable is assessed (Dahinten, Lee, & Macphee, 2016;Riley, Beal, & Lancaster, 2008).…”
Section: Structural Empowermentmentioning
confidence: 99%
“…Nurses need to be empowered because despite advances toward equality, they still feel oppressed, overwhelmed, and stressed. Negative nurse work outcomes including turnover have been linked to the work environment . Current literature identifies organizational characteristics, job demands, and lack of control over the practice as components of a negative work environment affecting nurse outcomes, but does not consistently provide a deeper look at the underlying reason for these issues .…”
Section: Contextmentioning
confidence: 99%
“…Workplace violence is a frequently occurring problem that contributes to burnout . Current studies report that 35% to 60% of nurses experience bullying in the workplace .…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…There is significant evidence that supports the link between empowerment and the following positive organizational consequences: job satisfaction, intent to leave, retention, patient satisfaction, interprofessional collaboration, adaptive resilience, enhanced work environment, patient‐safety culture, and work engagement . With a looming nursing shortage, the profession must turn to proven strategies for organizational success such as these.…”
Section: Actual Analysismentioning
confidence: 99%